The invaders : how humans and their dogs drove Neanderthals to extinction - Shipman, Pat, 1949- (The Belknap Press of Harvard University Press, 2015)
Humans domesticated dogs soon after Neanderthals began to disappear. This alliance between two predator species, Pat Shipman hypothesizes, made possible unprecedented success in hunting large Ice Age mammals--a distinct and ultimately decisive advantage for human invaders at a time when climate change made both humans and Neanderthals vulnerable.